2010
DOI: 10.1136/jnnp.2009.190652
|View full text |Cite
|
Sign up to set email alerts
|

Mefloquine in the treatment of progressive multifocal leukoencephalopathy

Abstract: Mefloquine, an antimalarial medication with efficacy against JC virus, was used to treat progressive multifocal leukoencephalopathy. A 54-year-old woman with sarcoidosis presented with a progressive cerebellar syndrome. MRI showed lesions affecting the right cerebellum that progressed over time to the brainstem. JC virus was found in the cerebrospinal fluid (CSF), and brain biopsy confirmed the diagnosis of progressive multifocal leukoencephalopathy. Mefloquine 1000 mg/week was initiated 6 months after symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 12 publications
0
51
1
1
Order By: Relevance
“…With respect to PML in patients without HIV, there are currently no approved therapies, although cytosine arabinoside, α-interferon, and cidofovir have been reported effective in some cases. Mefloquine, a widely used antimalarial agent, was recently reported to inhibit the JC virus infection in vitro (2) and produce some clinical improvement (3)(4)(5). Here, we report the beneficial effect of mefloquine in a case of PML associated with systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 83%
“…With respect to PML in patients without HIV, there are currently no approved therapies, although cytosine arabinoside, α-interferon, and cidofovir have been reported effective in some cases. Mefloquine, a widely used antimalarial agent, was recently reported to inhibit the JC virus infection in vitro (2) and produce some clinical improvement (3)(4)(5). Here, we report the beneficial effect of mefloquine in a case of PML associated with systemic lupus erythematosus (SLE).…”
Section: Introductionmentioning
confidence: 83%
“…Mefloquine is known to cross the BBB and accumulate in the brain, where JCV infection is pathological (221,388), but has been associated with neurotoxicity (493). Several independent case reports showed that mefloquine treatment of PML was successful in reducing the viral burden in the brain and was associated with improvement of clinical symptoms (168,244). However, as reported at the 2011 annual meeting of the American Academy of Neurology, a multicenter clinical trial supported by Biogen-IDEC Inc. and Elan Pharmaceuticals failed to show a reproducible reduction in the JCV DNA in PML patient CSF or reduced clinical progression of PML in response to mefloquine treatment (150).…”
Section: Treatment Of Pml and Pml-irismentioning
confidence: 99%
“…There are only very few case reports of mefloquine therapy in HIV-negative and HIV-positive patients with PML. These reports show positive results after the administration of mefloquine in PML [33,34,35]. The antimalarial agent mefloquine was tested in a small clinical trial (phase I and II) with some non-HIV patients, but mostly HIV-positive patients.…”
Section: Discussionmentioning
confidence: 99%